Analysis of Motor Vehicle Tax Amnesty Policy Related to Taxpayer Awareness in Increasing Taxpayer Compliance in Cianjur District - Amalia, Mia; Aulia Andini, Sifa; Ananda Potabuga, Trifika; Agustina, Tiara; Rachma Ardiani, Amelia (Universitas Djuanda, 2025)
In Cianjur Regency, Motor Vehicle Tax is one of the main sources of revenue. To increase the collection of this tax, one of the steps taken is the Motor Vehicle Tax Amnesty program. Compliance of Taxpayers has become a major issue that needs to be addressed in order to enhance Taxpayer awareness in paying taxes. Therefore, this research focuses on understanding how the Motor Vehicle Tax Amnesty policy affects Taxpayer awareness and compliance in Cianjur Regency, as well as the steps taken in its implementation. This study uses a qualitative method by collecting data related to the research objects and compiling it into a clear report. From 2021 to 2024, the revenue from Motor Vehicle Tax in Cianjur Regency continued to increase, especially after the tax amnesty policy was implemented. This indicates that taxpayers in Cianjur still have awareness of their obligation to pay taxes, and various efforts made have received a positive response regarding the importance of tax contributions.